Low-Dose Oral Contraceptives and Spontaneous Coronary Artery Dissection With Heavy Clot Burden in a Nonpregnant Woman - Gaspar Del Rio-Pertuz MD; Juthipong Benjanuwattra MD; Saif El Nawaa MD; Ankush Lahoti MD; Scott Shurmur MD (SAGE Publishing, 2022)
Spontaneous coronary artery dissection (SCAD) is an infrequent cause of acute coronary syndrome (ACS) caused by a nontraumatic tear in the coronary artery wall. The true incidence is thought to be underestimated owing to its diagnostic difficulty as coronary angiography is insensitive in assessing the arterial wall structure, thereby warranting additional diagnostic modalities such as intravascular ultrasound. We report a case of a young woman who had been taking oral contraceptives, and presented with acute non-ST segment elevation myocardial infarction due to SCAD with superimposed thrombosis.